Overall review of the overcapacity situation of China's thermal power industry: Status quo, policy analysis and suggestions. (September 2017) - Ming, Zeng; Ping, Zhang; Shunkun, Yu; Hui, Liu
Abstract: China's thermal power industry has gone through the phases of rapid development in the last decade. But the excessive enthusiasm of thermal power investment is making this industry overcapacity. The unbalanced demand-supply relationship in electric power market greatly affects the economic benefit of most thermal power plants. In this paper, we give an overall review of the overcapacity situation of China's thermal power industry, which is supported by latest data. Then, policy orientation and its effect is discussed. It can be found out that policies on the respect of construction scale control, renewable power integration, feed-in tariff reduction and environmental protection were considered as the main solution to relieve the over capacity situation. Finally, we propose three suggestions for the future development of China's thermal industry.